Paleomagnetic Logs: A Tool for Dating Lake Erie's Past - Mothersill, J.S; Schurer, P.J
An examination of the lithology, paleomagnetic and Mossbauer Effect Spectroscopy (MES) log data and 14C determinations of cores taken from three small basins located in western Lake Erie, in conjunction with data obtained from earlier studies, has been used to re-evaluate the postglacial history of the area. After the re-advance of the Laurentide Ice Sheet into the Huron basin and the eastern part of the Erie basin during the Port Huron stadial about 13,000 yrs B.P., lacustrine clay was deposited across much of the western Erie basin in a lake ponded against the glacial ice front to the east. However, by 12,000 yrs B.P. as the ice front retreated, the waters from the Huron basin bypassed Lake Erie, first by the Kirkfield outlet to Lake Ontario, and later by the Fossmill and North Bay outlets to the Ottawa River. This resulted in the draining of water from most of the western Erie basin. Extensive swamps choked with plants formed in the small basin areas, and the surrounding low-lying former lake bottom was subjected to subaerial weathering. It would appear that by about 9,500 yrs B.P. there was an increase in surface run off into these basins and the swamps evolved into shallow, relatively warm-water lakes in which calcareous-rich clay was deposited. Isostatic rebound of the northeastern outlets of the Huron basin led to a gradual tilting of the basin and a progressive migration of the southern shoreline of Lake Huron (Lake Stanley phase) to the southwest. By about 5000 yrs B.P. the water level in the southern Huron basin had been raised sufficiently to re-open the Port Huron outlet into the Erie basin. This resulted in a substantial rise in the lake level in the Erie basin, terminated the deposition of calcareous-rich clay in the small basins, and led to the deposition of normal lacustrine sediments in the modern phase of Lake Erie. J.S. Mothersill, P.J. Schurer. Obsahuje seznam literatury